Beyond Representation: Social Reconstruction of Traditional Fishermen and Coastal Reality in Sang Punggawa Laut Sumbawa - Ella Afnira; Andrie Ilham (CHANNEL: Jurnal Komunikasi, 2026)
This study aims to analyze the process of social reconstruction of traditional fishermen represented in the documentary film Sang Punggawa Laut Sumbawa. Rather than viewing the film solely as a medium of representation, this research positions it as a cultural text that constructs meanings about the social, economic, and cultural realities of coastal communities. The study employs a qualitative interpretive approach using Roland Barthes’s semiotic analysis, encompassing the levels of denotation, connotation, and myth, to examine how the identities and lived experiences of fishermen are reconstructed through visual and narrative signs. To strengthen interpretation, the findings are further contextualized through literature review and in-depth interviews with the Head of the Traditional Fishermen Community, maritime academics, and traditional fishermen in the Riau Islands. The results show that the film reconstructs fishermen not merely as marginalized coastal actors, but as adaptive social agents capable of negotiating structural inequalities through technological innovation, collective solidarity, and shifting family roles. Economic vulnerability is portrayed alongside resilience, while traditional values coexist with modernization processes. The transformation of gender roles within fishermen households also reflects changing social dynamics in coastal life. These findings demonstrate that documentary films can move beyond simple representation by articulating broader processes of social change and reconstruction within marginalized communities. This study offers an analytical perspective that links media texts to the reconstruction of social realities, while reaffirming documentary film as an important medium for understanding the collective experiences of Indonesian traditional fishermen.